Morphometric study of horseshoe crab’s spawning population in a coastal area of peninsular Malaysia - Md Razak, Mohd Razali; Syazz, Wan; Zaleha, Kassim (2022)
Two Asian horseshoe crabs Tachypleus gigas and Carcinoscopius rotundicauda are commonly found on some coastal habitat in the east coast of Peninsular Malaysia during their spawning season. The number is small if compared to the Atlantic species, Limulus polyphemus which could be related to their foraging ground on sea bottom. It is not easy to ascertain the reason of the small landing population of horseshoe crab in the east coast of the Malay Peninsula. Some morphometric information on spawning population of horseshoe crab was studied at mangroves and sandy beach habitat in Balok coastal area of Pahang. Morphometric parameters measured in this study included body weight (Wt), inter-ocular length (IOL), dorsal prosoma breadth (DPB), dorsal body length (DBL), ventral prosoma breadth (VPB), telson length (TL), central height (CH), frontal length (FL), frontal margin height (FMH), and regional length (RL). Weight of T.gigas ranged from 290 to 1200g and 180 to 420g for female and male respectively while C. rotundicauda ranged from 260 to 340g and 100 to 260 for female and male respectively. Parameter with the highest mean value is weight. The lowest mean value was found for IOL with 88.64±6.62mm (male) and 120.42±9.95mm (female) and 62.87±14.39mm (female) and 77.0±6.57mm (male) for T.gigas and C. rotundicauda respectively. Statistically it was found that the males and females T. gigas could grow with the same rate in DPB and DBL. Nonetheless, male C. rotundicauda has the most increase of size of prosomal breadth in DPB than DBL. There was no evidence of imbalance growth of both sexes of the species collected from the study area. The findings indicate a good growth condition for both species. The relationship between the surrounding bottom habitat and the diet of horseshoe crab should be studied further to understand the contribution of sea bottom habitat to horseshoe crabs.